Assessing Mental Health and Psychological Wellbeing in Medical Students: A Systematic Review (European Journal of Behavioral Sciences, 2024)
Medical students' psychological wellbeing is a growing concern. However, the methods used and outcomes measured in studies evaluating psychological wellbeing lack consistency given their wide and diverse array. This systematic review aims to characterise and comprehensively evaluate the outcomes measured and methods used in studies assessing psychological wellbeing among medical students. A consensus on the constructs and methods used in indexing psychological wellbeing can lead to more effective assessments and consequently more effective interventions aimed at promoting wellbeing in medical students. Methods: Multiple databases were searched, including Medline, PsycINFO, Cochrane Library, and Web of Science. Grey literature was searched through Google Scholar, and reference lists of the included studies were further searched. Results: Forty-five studies were included, and findings were integrated into a narrative synthesis. The results showed that various methods were used and various outcomes were measured to index medical students’ mental wellbeing; outcomes tapped on stress, depression, anxiety, burnout, and minor psychiatric disorders as wellbeing indicators while commonly used measures were the General Health Questionnaire, Oldenburg Burnout Inventory, Perceived Stress Scale and Depression Anxiety Stress Scale. Self-reported measures and quantitative designs predominated, focusing on negative indicators of wellbeing. The findings of this systematic review highlighted the vast heterogeneity in outcomes measured and methods used in studies assessing psychological wellbeing in medical students. Conclusions: Homogeneity in the measures and outcomes used to assess wellbeing is necessary to improve the comparability and reliability of findings among studies. Future research should also use validated measures that capture both positive and negative aspects of psychological wellbeing to gain a more comprehensive understanding of the factors that can promote positive psychological wellbeing; and consequently, to inform the development of more effective interventions tailored to the mental health needs of medical students.